IMPLEMENTATION OF RISK ASSESSMENT TO IDENTIFY DAMAGE OF SEMARANG STATIC ARCHIVE PAPERS IN ANRI - Ardiansyah, Aditya R.; Susiani, Susiani; Sriyanto, Widi (P3M Politeknik Negeri Media Kreatif, 2023)
Risk Assessment is a process of identifying and analyzing risks to determine the level of threat/danger to archive damage. The results of the Risk Assessment activities can be used to formulate archive preservation policies and strategies in carrying out preservation actions both preventively and curatively. The Risk Assessment activity is an activity that is expected to make it easier to determine steps in prevention, repair, maintenance of physical archives in general, including the information contained therein and can be used to formulate policies. The purpose of writing this final project is to determine the parameters observed in the risk assessment process of Semarang static archival paper, and determine the extent of the damage so that it can be used as a reference to determine whether restoration and reproduction are necessary. The risk assessment steps carried out consist of preparation, implementation and evaluation. Parameters observed in the risk assessment process of Semarang static archive paper included the shape of the binding and the causes of damage to archival documents caused by chemicals, pests and water stains. The results of the archival paper risk assessment show that the document has a high level of damage and is very vulnerable and easily broken so restoration activities are needed. The factors that cause the most damage to archival paper are insects, ink corrosion, foxing stains and acidification